Salinity patterns and local migration determine the isotopic composition of the invasive blue crab, Callinectes sapidus, along the Spanish Mediterranean coast - Patricia Prado; Iraida Català; Carles Alcaraz; Maria del Carmen Barberà; Elena Guijarro-García; Silvia Falco (PLoS ONE, 2025)
δ13C and δ15N patterns of the blue crab, Callinectes sapidus, and its potential diets, were investigated in eleven localities within four invaded regions of the Spanish Mediterranean (Catalonia, Valencia, Alicante, and Murcia) subjected to contrasting salinities and degrees of connectivity with the open sea. These regions host blue crab fisheries of variable importance that might be regulated by availability of food resources and local environmental conditions. When present, large adults and immature, subadult sizes of each sex were captured to evaluate possible differences associated to age movement across habitats. SIBER and MixSIAR were used to assess patterns of isotopic niche and dietary contributions. Results showed significant effects for all factors and interactions (except for Sex and Sex x Size in δ15N). The effect size in Region (ηp2 = 0.82 and 0.70, respectively for δ13C and δ15N) and Locality (ηp2 = 0.53 and 0.46), was substantially greater than that of crab Size (ηp2 = 0.37 and 0.21) and Sex (ηp2 = 0.06 and 0.02), concurring with increasing levels of isotopic niche overlap (9% and 11% in Locality and Region, 32% in Size and 44% in Sex). MixSiar results indicated strongly variable contributions from food sources at each locality (TPs from 2.3 to 3.6), but with higher quantity of fish, algae, and crustaceans (27.7%, 18% and 15.1%). Dietary results showed little relation with isotopic patterns, whereas significant associations were found between local salinities and signatures in both crabs (R2 = 0.518 and 0.757, for δ13C and δ15N) and diets. Overall, our study suggests that blue crab habitat use in small Mediterranean estuaries might largely differ from native areas, with movements being mostly restricted to young individuals and/ or certain localities with higher connectivity with the open sea (e.g., the Ebro River). Salinity conditions emerge as a major variable shaping isotopic patterns of populations on a large scale.